Does the State Civil Apparatus Violate Neutrality During Elections? - Nadzirin, Akhwan; Mawarini Sukmariningsih, Retno; Mashari, Mashari (Lembaga Contrarius Indonesia, 2025)
The impartiality of the State Civil Apparatus (ASN) is a fundamental prerequisite for ensuring free, fair, and democratic elections in Indonesia. As a complex legal topic encompassing constitutional rights, regulatory concerns, and bureaucratic politics, the goal of this study is to examine infractions of ASN neutrality. This research explores violations of ASN neutrality as a complex legal issue intersecting constitutional rights, regulatory shortcomings, and bureaucratic politicization. Employing a normative-empirical legal approach, the research draws on statutory analysis and field data from three districts Karanganyar, Boyolali, and Kendal. The findings reveal three critical legal and structural problems. First, enforcement of neutrality norms is undermined by fragmented, overlapping regulations and weak sanction mechanisms, reflecting a significant legal gap in the regulatory framework. Second, a normative conflict exists between the ASN's obligation to remain neutral and their constitutional political rights as citizens, particularly regarding passive political expression in private settings. This tension raises concerns over the proportionality and legitimacy of current restrictions. Third, the politicization of the bureaucracy by incumbent regional leaders has institutionalized patronage and structural pressure, weakening meritocracy and professional independence. The research recommends codifying ASN neutrality under a unified, enforceable legal framework; redefining the boundaries of political rights and professional duties; and strengthening institutional safeguards to protect civil servants from political coercion. Upholding both neutrality and civil liberties is essential to sustaining democratic governance and restoring public trust in the bureaucracy.